Classification of actuation mechanism designs with structural block diagrams for flapping-wing drones: a comprehensive review - Singh, Spoorthi; Zuber, Mohammad; Hamidon, Mohd Nizar; Mazlan, Norkhairunnisa; Basri, Adi Azriff; Ahmad, Kamarul Arifin (Elsevier, 2022)
Flying insects are interesting dipteras with an outstanding wing structure that makes their flight efficient. It is challenging to mimic flying insects and create effective artificial flapping drones that can imitate their flying techniques. The smaller insect-size drones have remarkable applications, but they need lightweight and minimal connecting structures for their transmission mechanism. Many operating methods, such as the traditional rotary actuation method and non-conventional oscillatory mechanisms with multiple transmission configurations, are popularly adopted. The classification and recent design innovations with flapping actuation mechanism challenges, particularly bio-inspired (biomimetics) and bio-morphic types of flapping-wing aerial vehicles from micro to pico-scale, are discussed in this review paper. For ease of understanding, we have attempted to depict the actuation mechanisms in the form of block diagrams. The ability of hybrid efficient mechanisms to improve the flapping frequency of wings and flapping actuation design process, including other parameters, such as flapping angle, lift generation, and hovering ability with current driving mechanisms, is also discussed. Depending on their endearing resemblance, we have segregated Flapping-Wing Micro Air Vehicle (FWMAV) design patterns like birds, small birds, nano hummingbirds, moths, bats, biomorphic types, flapping test bench models, and fully flyable models, which are characterized by their flight modes. Important flapping actuation systems that can be used to achieve hovering capability are highlighted. The actuation mechanisms' specifications and configurations are expanded by focusing on the need of flapping frequency and stroke angle controllability via the linkage mechanisms with insight into flapping patterns. Besides that, the requirements for the sustainability of flying patterns during manual and automatic launches were investigated. In addition, the different researchers' annual progress on their Flapping-wing models has been emphasized. The best performing prototypes with their flapping actuation mechanism contributions to achieving better lift and long-duration flight sustainability are articulated through ranking. An insight into some of the significant challenges and future work on flapping performance levels are also discussed.